A secondary abdominal pregnancy with unusual placental implantation in the fallopian tube: a diagnostic challenge - Algeri Paola; Nicoli Elena; Rota Sonia Maria; Caruso Orlando; Manfredini Cinzia; Buzzi Antonella (Korean Society of Obstetrics and Gynecology, 2018)
We reported a case of secondary abdominal pregnancy with placental implantation into the fallopian tube, diagnosed at 16 weeks, in a woman admitted to the emergency room complaining of syncopal attacks. The best approach would be termination of the pregnancy, taking into consideration the high risk to the mother and the low possibility of alive and healthy birth. We had to perform an urgent surgical intervention due to the fact that the patient was in a clinically unstable condition, which was related to hemoperitoneum. If placental implantation is on abdominal organs or vessel the best approach would be to ligate the cord and to leave placenta in situ. Taking into consideration the place of placental implant, the removal of the fallopian tube with the placenta was the safest approach in this case. The best and most acceptable form of treatment would be individualized in case of rare form of ectopic pregnancy.